First Language Attrition: What It Is, What It Isn’t, and What It Can Be - Gallo, Federico; Bermudez-Margaretto, Beatriz; Shtyrov, Yury; Abutalebi, Jubin; Kreiner, Hamutal; Chitaya, Tamara; Petrova, Anna; Myachykov, Andriy (Frontiers in Human Neuroscience, 2021)
This review aims at clarifying the concept of first language attrition by tracing its limits, identifying its phenomenological and contextual constraints, discussing controversies associated with its definition, and suggesting potential directions for future research. We start by reviewing different definitions of attrition as well as associated inconsistencies. We then discuss the underlying mechanisms of first language attrition and review available evidence supporting different background hypotheses. Finally, we attempt to provide the groundwork to build a unified theoretical framework allowing for generalizable results. To this end, we suggest the deployment of a rigorous neuroscientific approach, in search of neural markers of first language attrition in different linguistic domains, putting forward hypothetical experimental ways to identify attrition's neural traces and formulating predictions for each of the proposed experimental paradigms.